National Survey on Access, Use and Promotion of Rational Use of Medicines:: methods - Álvares, Juliana; Alves, Maria Cecilia Goi Porto; Escuder, Maria Mercedes Loureiro; Almeida, Alessandra Maciel; Izidoro, Jans Bastos; Guerra Junior, Augusto Afonso; Costa, Karen Sarmento; Costa, Ediná Alves; Guibu, Ione Aquemi; Soeiro, Orlando Mario; Leite, Silvana Nair; Karnikowski, Margô Gomes de Oliveira; et al. (Revista de Saúde Pública, 2017)
The Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services) aimed to characterize the organization of pharmaceutical services in the Primary Health Care of the Brazilian Unified Health System (SUS). PNAUM – Services is a cross-sectional and evaluative study, with planned sample of 600 cities, held between 2014 and 2015, composed of a remote phase, with telephone interviews with health managers. Of these 600 cities, 300 were selected for a survey on health services. We selected the 27 capitals, the 0.5% largest cities of each region, and the remaining cities were drawn. The estimate of the representative national sample size considered three levels: cities, medicine dispensing services, and patients. The interviews were carried out with a structured questionnaire specific for: municipal secretaries of health, professionals responsible for pharmaceutical services in the city, professionals responsible for the dispensing of medicines, physicians, and patients. The secondary data were obtained in official databases, in the latest update date. PNAUM – Services was the first nationwide research aimed at the assessment and acquisition of national and regional indicators on access to medicines, as well as use and rational use, from the perspective of various social subjects